Phosphate Concentration from the Water around the Floating Cage Fish Culture Area and from the Area with No Cage, in the DAM Site of the Koto Panjang Reservoir - Ali Akbar Navis; Asmika H. Simarmata; Clemens Sihotang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
In floating cage fish culture activities, degradation of feed remain and fish feces willincrease the Phosphate content in the surrounding area. A research aims to understand thePhosphate concentration in the water from the cage area and from the area that has no cage hasbeen done from July - November 2014. There were 3 stations, namely 200 m upstream nof thecage area (S1), in the cage area (S2) and 200 m downstream of the cage area (S3). Samplingswere conducted in the DAM site 4 times, once/2 weeks. In each station, water samples werecollected from 3 different depth, surface; 2 secchi and 4 secchi depths. Parameters measuredwere pH, Phosphate concentration, Dissolved Oxygen, transparancy, temperature and depth.Results shown that the concentration of Phosphate in the S1was 0.03 mg/L – 0.13 mg/L; in theS2 was 0.13 mg/L – 0.35 mg/L; and in the S3 was 0.07 mg/L – 0.22 mg/L. The highestconcentration of the Phosphate was in S2, while the lowest was in the upstream (S1). Phosphateconcentration indicates that the DAM site area of the Koto Panjang can be classified aseutrophic, especially in the area around the cage. Other water quality parameter measured weretemperature: 30.6oC – 31oC; transparancy 1.98 m – 2.55 m; depth 27 m – 40 m; pH 5 and freeCO2: 4.66 mg/L- 15.31 mg/L. the values of water quality parameters indicate that the waterquality in the DAM site of the Koto Panjang is good and might be able to support the life ofaquatic organisms in thet area.Keywords: phosphate, cage fish culture,Koto Panjang Dam